High-risk endometrial cancer in young indigent women. Issue 5 (1st August 2004) - Ben-Arie, A.; Perlman, S.; Hazan, Y.; Solomon, L. A.; Edwards, C.; Kaplan, A. L.
Abstract : Objective: The aim of this study was to evaluate a different prevalence and clinical pattern of high-risk endometrial cancer in an indigent population of young women. Methods: Charts of 71 consecutive patients, treated for endometrial adenocarcinoma during a 6-year period, were reviewed. The patients were divided into two groups contingent upon age – (i) those who were below 40 years and (ii) those who were over 40. Based on histological type, grade, and stage, both groups were subdivided into a low, intermediate, or high-risk cancer category. Results: Of the 13 (18.3%) patients in the younger age group, five patients (38.4%) had high-risk endometrial cancer, compared to only eight patients (13.8%) in the older age group. Conclusion: In contradiction to previous reports, our results show that a higher proportion of young indigent women diagnosed with endometrial cancer have a high-risk cancer. Delay in diagnosis can explain only some of the discrepancies in the special clinical pattern of endometrial cancer among this population. Other possible explanations include nutritional differences, genetic susceptibility, immunological status, and high-risk behavior. More epidemiological studies are needed for complete understanding of the unfavorable outcome of endometrial cancer in these young women.